The Potential of Implementing Website-Based Learning Media for ESD-Oriented Energy Sources in Physics Learning - Suminarsih, Suminarsih; Khoiri, Nur; Harto Nuroso; Muhammad Syaipul Hayat (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study aims to analyze the potential of implementing ESD (Education for Sustainable Development) oriented website-based learning in Physics learning. This research is a qualitative descriptive study. Questionnaires, observation, and documentation methods were chosen as data collection techniques. The results of data collection were analyzed using data triangulation. The survey results showed that 86% of teacher respondents were in the proficient or very proficient category, which indicates a high readiness to adopt website-based learning media. Although related to the implementation of ESD in learning, it shows that 45% of teachers have integrated ESD in their learning, 41% of teachers have understood the concept of ESD but have not integrated ESD in learning, and 14% of teachers have not understood the concept of ESD in learning. These results indicate a great opportunity to strengthen the understanding and practice of ESD through the development of website-based teaching materials. This data is supported by the results of the student questionnaire which showed that as many as 20 of 22 students (91%) agreed or strongly agreed that the use of digital media in learning provides benefits. These results show that most students have experience and comfort in digital-based learning. The results of the questionnaire show that both teachers and students have positive perceptions and readiness in integrating digital technology, especially website, in ESD oriented Physics learning. Development website Interactive and ESD-oriented Physics learning is a strategic step to improve the quality of learning in the digital era.